2020
DOI: 10.11648/j.sjams.20200803.11
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis of HIV/AIDS Patients Under ART Follow up in Attat Referral Hospital

Abstract: Background: The non-curable HIV/AIDS epidemic has become a serious health and development problem especially for developing country like Ethiopia despite using ART treatment. The antiretroviral treatment (ART) scale-up service has been a recent development in Ethiopia, but its impact on mortality has not been well investigated. This study aimed to analyze the survival time of HIV-positive patients under antiretroviral therapy (ART) and identifies associated risk factors in Attat Referral Hospital. Methods: A r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
2
1
Order By: Relevance
“…27 In contrast to this, our study finding was higher than the study conducted from six Asia-Pacific countries that reported lower death rate of 5.3%, 23 in India of 2% 28 and in Europe of 4.7%. 27 However, our study finding is lower than a collaborative follow-up study conducted in South Africa which revealed 16.6% 27 and 29.7% death rate was reported at Attat Referral Hospitals, Gurage Zone, Ethiopia 10 as well as 16% in Illubabor and Buno-bedele zone. 8 This might be due to an improved care of opportunistic infections at facilities and the way of lifestyle that directly or indirectly affect the health seeking behavior of the patients.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…27 In contrast to this, our study finding was higher than the study conducted from six Asia-Pacific countries that reported lower death rate of 5.3%, 23 in India of 2% 28 and in Europe of 4.7%. 27 However, our study finding is lower than a collaborative follow-up study conducted in South Africa which revealed 16.6% 27 and 29.7% death rate was reported at Attat Referral Hospitals, Gurage Zone, Ethiopia 10 as well as 16% in Illubabor and Buno-bedele zone. 8 This might be due to an improved care of opportunistic infections at facilities and the way of lifestyle that directly or indirectly affect the health seeking behavior of the patients.…”
Section: Discussioncontrasting
confidence: 84%
“…Data collection format was prepared in English version by reviewing from the national ART intake and follow-up forms and different similarly literatures. 9,10,13,16 Socio demographic data (marital status, sex, age, occupation, residence, and educational status), baseline data, and laboratory data were collected by reviewing pre-ART registers (like sociodemographic data), ART intake forms, laboratory requests, individual patient's folder and monthly follow-up charts by experienced data collectors and daily activities of data collection team evaluated by principal investigators. The most recent laboratory test before initiation of ART was used as a baseline data.…”
Section: Data Collection Tools and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation